Parental Social Support on Students’ Adjustment - Maulana Fathur Rahman; Menik Tetha Agustina (Faculty of Psychology, Universitas Semarang, 2024)
Self-adjustment is an important aspect for new students in dealing with changes in the lecture environment. This study aims to examine the relationship between parental social support and students' self-adjustment ability. Specifically, this study plans to investigate the extent to which parental social support affects the self-adjustment ability of new students of the Faculty of Psychology, Universitas Nasional Karangturi Semarang. This study employed a quantitative survey approach involving 75 students as respondents. The research instruments consisted of a parental social support scale and a self-adjustment scale, which each had a reliability coefficient of α =0.774 and α =0.902. The data were analysed using the Pearson correlation test with the assistance of the SPSS software version 26. The results showed a positive and significant relationship between parental social support and self-adjustment of new students (r=0.261, p=0.023). These results indicate that the higher the parental social support received by students, the better their ability to adjust in the academic environment. This finding confirms the important role of parental support in helping new students adapt during the transition to university life. Keywords: Parental Social Support; Self-Adjustment; Students